(untitled) - Trần, Thuý Kiều (Cần Thơ, 2010)
The reasons mention above, the specific aims of the study are:(1) to explore how students studying at Can Tho University use lerning technology in their self-directed learning; (2) to find out students' view about teachers' supporting learning through technology; (3) to suggest some implications to improve the quality of using learning teachnology in in studends self-directed learning.
Keywords: Educational technology,Công nghệ giáo dục,Learning,Internet in education,Sự học,Internet trong giáo dục